Pengaruh Motivasi Kerja dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan Pada PT. Bringin Karya Sejahtera Kantor Cabang Denpasar - I Ketut; Ida; Cokorda (PROSENAMA, 2024)
This research aims to determine the job satisfaction of PT employees. Bringin Karya Sejahtera Denpasar Branch Office. Job satisfaction not only determines employee welfare, but also has a significant impact on company performance and sustainability. By understanding the factors that influence job satisfaction, companies can design more effective strategies to increase productivity and retain quality employees. This research uses a quantitative approach with a survey method involving 35 employees from various positions in the company. The research results show that partial work motivation on job satisfaction shows an influence that is not positive and not significant. Meanwhile, the work environment partially shows a positive and significant influence on job satisfaction. Simultaneously, work motivation and work environment show a positive and significant influence on employee job satisfaction. The conclusions of this research underline the important role of work motivation and work environment in increasing employee job satisfaction. These findings provide practical implications for PT management. Bringin Karya Sejahtera Denpasar Branch Office to focus on improving motivational aspects and creating a conducive work environment. By paying attention to these two factors, companies can increase job satisfaction which in turn will have a positive impact on individual and overall organizational performance. This research also opens up opportunities for further studies to explore other variables that can influence job satisfaction, such as leadership, organizational culture, and work-life balance.